The Myth of the “Latin Island” and Romania’s Strategic Culture. An Attempt to Interpret Romania’s Policy Towards Ukraine After the Russian Invasion in 2022 - Oleksy, Piotr (Sensus Historiae, 2023)
The article attempts to explain the specifics of Romania’s policy toward Ukraine after the Russian invasion of the country. The author traces the origins of this policy to the myth of the “Latin island,” which was the main founding myth for the Romanian national community. It evokes certain foreign policy attitudes: a desire to stay in the mainstream of Western politics, a perception of Russia as a threat to one’s sovereignty, and a distance from the Eastern Slavs in general. The author points out that these defined both the conservative policy toward Ukraine immediately after the Russian invasion and the rapprochement in mutual relations that occurred in the fall of 2023.